2019
DOI: 10.1039/c9dt02394a
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of nanoscale cobalt(ii)-based MOFs: highly efficient photo-induced green catalysts for the degradation of industrially used dyes

Abstract: Solvothermally synthesized CoII based MOFs have been exploited as visible light induced dye degradation catalyst having real life applicability where introduction of H2O2 enhances the efficiency markedly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…The dye elimination process follows first-order kinetics ( C 0 is small): RhB, MB, ARB, and AY17 all follow the equation where C t is the dye solution concentration at time “ t ”, C 0 is the dye solution concentration at t = 0, and k is the rate constant. The calculation formula of dye degradation efficiency is degradation efficiency (%) = [( C 0 – C t )/ C 0 ] × 100%. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dye elimination process follows first-order kinetics ( C 0 is small): RhB, MB, ARB, and AY17 all follow the equation where C t is the dye solution concentration at time “ t ”, C 0 is the dye solution concentration at t = 0, and k is the rate constant. The calculation formula of dye degradation efficiency is degradation efficiency (%) = [( C 0 – C t )/ C 0 ] × 100%. , …”
Section: Methodsmentioning
confidence: 99%
“…The calculation formula of dye degradation efficiency is degradation efficiency (%) = [(C 0 − C t )/C 0 ] × 100%. 22,23 ■ RESULTS AND DISCUSSION Crystal Structure Description of CUST-560…”
Section: ■ Introductionmentioning
confidence: 99%
“…MV/RhB UV light 73.3/55.1 CNNSs/MIL-100(Fe) [109] RhB Visible light + H 2 O 2 100 N-Cu 2 O/carbon composites [110] MO Visible light 90 [{Co(5NH 2 -IPA)(1,2-bpe)}] 1 [111] RhB/MB Visible light + H 2 O 2 98/96 [Co 2 (1,4-BDC)(NCP) 2 ] [112] MV UV light 33.29 [Co 2 (4,4'-Hcpmb)(1,3-bib)] [113] MV UV light 94.7 [Co(bpco) 0.5 (tib)(H 2 O) 2 ] [114] MV UV light 55 [Mn 2 (μ 2 -H 2 O)(H 2 L)(CH 3 CN) 2 ] [115] MV UV light 51.73 [Mn(L) 0.5 (phen) • 0.5H 2 O] [115] MV UV light 55.31 MOF-5/LTH [116] MB UV-visible light 98.1 [Zn(L)(4,4'-bipy) • CH 3 CN] n [117] MV/RhB UV light 60.6/29.4 2D-CuTCPP [100] RhB Visible light 81.2 Co@NC-600 [118] MB/ RhB NaBH 4 99.9/95.7 nanosheet, of which the TC degradation efficiency can reach 73% within 5 min under visible light. In addition, Zhao's team reported a rapid microwave-assisted hydrothermal route for the assembly of 2D copper-porphyrin MOFs (Cu-TCPP MOFs) within an hour.…”
Section: MVmentioning
confidence: 99%
“…Among them, degradation of organic dyes by complexes has attracted more and more attention in recent years. For instance, Das et al [ 29 ] synthesized two Co (II)‐based complexes, with excellent photocatalytic efficiency to degrade RhB and MB. Adhikary et al [ 30 ] reported a porous Zn(II)‐based complex, which can photocatalytic degradation of RhB and MB under ultraviolet illumination.…”
Section: Introductionmentioning
confidence: 99%